Juridical Observation towards the agreement of purchase contract without notary public in Banggai Kepulauan - Fahryansyah, Yan; Arfah Pattenreng, Andi Muhammad; Madiong, Baso (Postgraduate Bosowa University Publishing, 2018)
This study aims to analyze and understand the causes of the sale and purchase agreement without notary public and the legal consequences in Banggai Kepulauan District and the legal power of land purchase agreement without notary public if there is a dispute. This type of research was empirical juridical. The results showed that the implementation of the sale and purchase agreement without notary public in Banggai Kepulauan Regency is still a choice due to the culture / customs of local people, the limited cost, the fast time, and the process does not take a long time. Implementation of the sale of land without notary public in Banggai Kepulauan Regency is proceeded through three ways; trust, a receipt, and a proof made by Village Head. While the legal force of the sale and purchase of land without notary public in Banggai Kepulauan Regency is still valid, but for legality it not yet valid because there is no certificate.